Comparison of three salivary flow rate assessment methods in an elderly population - Jones JM, Watkins CA, Hand JS, Warren JJ, Cowen HJ (Blackwell Synergy, 2000)
Measuring salivary flow rates among the frail elderly is a challenge. The currently used spit collection method requires levels of time and cooperation that often may exclude the frail elderly who are at high risk for salivary compromise. A measurement method that is not only valid and reliable, but also feasible and acceptable is needed for use in population studies of compromised adults.